PC3 - 155 Phase II Study of Dianhydrogalactitol in Patients with MGMT-Unmethylated, Bevacizumab-Naïve Recurrent Glioblastoma. (18th October 2016) - O'Brien, B.J.; Bacha, J.A.; Brown, D.M.; Steino, A.; Schwartz, R.; Kanekal, S.; Lopez, L.M.; Penas-Prado, M.
Abstract : Glioblastoma (GBM) is the most common brain cancer. Most GBM tumors have unmethylated promoter status for O6-methylguanine-DNA-methyltransferase (MGMT); a validated biomarker for MGMT protein-expression and ensuing temozolomide-resistance. Second-line treatment with bevacizumab has not improved overall survival (OS). Dianhydrogalactitol (VAL-083) is a bi-functional alkylating agent targeting N7-Guanine, thus MGMT-independently inducing interstrand cross-links, DNA double-strand breaks and cell-death in GBM cell-lines and cancer stem cells. VAL-083 is currently in Phase I/II clinical trial for recurrent GBM, post-TMZ and post-bevacizumab. In this Phase II clinical trial, the main goal is to assess the 9-month OS in MGMT-unmethylated, recurrent, bevacizumab-naive GBM. RATIONALE: The vast majority of GBM patients experience recurrent/progressive disease within a year from initial diagnosis and median survival after recurrence is 3-9 months. Chemotherapy regimens for these patients are lacking and there is a significant unmet medical need. Given VAL-083's novel alkylating mechanism, promising clinical benefit, and favorable safety profile, a trial studying VAL-083 in MGMT-unmethylated recurrent GBM is warranted. METHOD: Randomized, non-comparative biomarker-driven Phase II clinical trial in MGMT-unmethylated GBM patients at first recurrence/progression, prior to bevacizumab. 48 patients will be randomized to receive VAL-083 or "standard-of-care" salvage drug lomustine. 32 patients will receive VAL-083 40mg/m2/day on days 1, 2, 3 of a 21-day cycle. 16 patients will receive lomustine 90 mg/m2/day on day 1 of a 42-day cycle. Patients will be followed until death or for at least 9 months from enrollment, whichever occurs earlier. Survival will be compared to the BELOB trial for recurrent MGMT-unmethylated GBM patients treated with lomustine.